Analysis of the Effect of Government Expenditures, Inflation, and Labor on the Economic Growth of the City of Palangka Raya - Istighfaris Rezki; Andrie Elia Embang; Luluk Tri Harinie (Journal Magister Ilmu Ekonomi Universtas Palangka Raya : GROWTH, 2018)
ABSTRACTThis study analyzes the effect of government spending, inflation, and labor on the economic growth of the City of Palangka Raya. The analysis was performed statistically using multiple linear regression equation models and secondary data in line with the time period between 2002-2016. The results of the analysis conclude that partially government expenditure variables have a positive and significant effect on the economic growth of Palangka Raya City, the inflation variable has a positive but not significant effect on the economic growth of Palangka Raya City, and labor variables have a positive and significant effect on the economic growth of Palangka Raya City.